1997
DOI: 10.1002/(sici)1098-2825(1997)11:2<78::aid-jcla2>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of four methods for the diagnosis of acute infection by Epstein‐Barr virus

Abstract: We studied the reliability of new indirect tests in the diagnosis of acute infection by Epstein-Barr virus (EBV). Studied for all samples were: method 1, the heterophil antibodies (Abs) (Monolatex, Biokit, Germany); method 2, the IgM Abs to EBV with ELISA tests (antigen pools, Enzygnost, Behringwerke, Germany); method 3, EA (Biotest Diagnostics, Germany); and method 4, the IgG avidity test. The reliability of the four tests for the detection of primary infection by EBV was: sensitivity (method 1: 89.1%; method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…The Enzygnost EBV kit uses several lymphocyte-expressed antigens. In previous studies that compared Enzygnost with different methods (14,22), we found a good correlation with other ELISA or IFA methods that use only VCA. Enzygnost has optimal diagnostic reliability as long as patients with clonal stimulation of B cells are excluded.…”
Section: Value Of Igm Titers With Enzygnost In the Diagnosis Of Recent Acute Infectionsupporting
confidence: 65%
See 1 more Smart Citation
“…The Enzygnost EBV kit uses several lymphocyte-expressed antigens. In previous studies that compared Enzygnost with different methods (14,22), we found a good correlation with other ELISA or IFA methods that use only VCA. Enzygnost has optimal diagnostic reliability as long as patients with clonal stimulation of B cells are excluded.…”
Section: Value Of Igm Titers With Enzygnost In the Diagnosis Of Recent Acute Infectionsupporting
confidence: 65%
“…However, indirect diagnosis does not detect all actual illnesses because the antibodies may be absent, or may occur in situations of the clonal stimulation of B lymphocytes (due to a present infection by another pathogenic agent) (6)(7)(8)(9)(10)(11). Different authors (12)(13)(14)(15) have tried to solve some of these diagnostic problems by detecting sera IgG without avidity for the antigen (Ag), which is present in primary infections, although the absence of IgG and the rapid increase in its affinity for the antigen reduce the diagnostic reliability of this test.…”
Section: Introductionmentioning
confidence: 99%
“…One of such systems is the BACTEC system, which uses non invasive fluorescent technology to detect increases in Co 2 produced by the microbial growth. The performance of such a system is influenced by several factors including the volume of blood samples, the use of resins shaking to increase the recovery of aerobic microorganisms, duration of incubation, and final subculture [10].…”
Section: Introductionmentioning
confidence: 99%